How Internet Technology Can Improve the Quality of Care for Substance Use Disorders - Cucciare, Michael A.; Weingardt, Kenneth R.; Humphreys, Keith (Current Drug Abuse Reviews, 2009)
By allowing for the efficient delivery of instructional content and the secure collection of self-report data regarding substance use and related problems, the Internet has tremendous potential to improve the effectiveness and accessibility of addiction treatment services. This article discusses some of the ways in which Internet technology can facilitate, complement and support the process of traditional clinician-delivered treatment for individuals with substance use disorders. Internet applications are being used to support a range of activities including (a) the assessment and feedback process that constitutes a central feature of brief motivational interventions, (b) the concurrent monitoring of individual level outcomes among patients who are currently enrolled in addiction treatment programs, (c) the continuing care and ongoing recovery of patients who have completed treatment, and (d) the delivery of clinical training in evidence based practices for addiction treatment providers. This emerging body of literature suggests that addiction counselors and program administrators can enhance the quality of clinician-delivered treatment by incorporating internet applications into existing processes of care. Internet applications provide an unparalleled opportunity to engage patients in the treatment process, incorporate real-time data into treatment planning, prevent relapse, and promote evidence-based treatment approaches.
Keywords: mental health recovery